The encounter with clove flower buds / Ibtisam Abdul Wahab, Hannis Fadzillah Mohsin and Mohamad Rahimi Sulaiman - Abdul Wahab, Ibtisam; Mohsin, Hannis Fadzillah; Sulaiman, Mohamad Rahimi (Universiti Teknologi MARA, Negeri Sembilan, 2024)
There are about 1200 species of plants in the Syzygium genus, belonging is well known as the clove orto the Myrtaceae family. Syzygium aromaticum cengkih, in Malay (Figure 1). The most important organ of S. aromaticum that is involved in folk medicines and traditional practices is the Faculty of Pharmacy, UiTM, the pharmacognosy lessons in the fifth week of the semester would include the introduction to clove oil as an example of a non-glyceride lipid. The brown clove flower buds are subjected to experimental and laboratory procedures, such as the introduction of the oil in plants. Pattamadilok et al. (2021) established a quality specification of Thai clove samples by determining their physicochemical characteristics.